Les énergies marines renouvelables répondent-elles au modèle d’économie de la fonctionnalité ? - Soazig Lalancette; Pascal Le Floc’h; Bertrand Le Gallic (VertigO)
This article seeks to estimate the relevance of the service economy applied to marine renewable energy projects. This study is based on stakeholder contributions in public debate in Saint-Brieuc offshore wind farm project (France). We seek to analyze stakeholder perspectives through an application of a textual analysis on contributions (cahiers d’acteurs). Textual analysis reveals two main results, the first one turns to social and economic question with the impact on the territory, in particularly the employment and the training. The second issue concerns the energy efficiency of marine renewable technologies. For each of these issues, the discussion try to give a perspective regard to service economy theory and discuss about the relevance of service economy application in marine renewable energy sector.